2021
DOI: 10.3390/ijms22031424
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miRNAs, miRNA Clusters, and isomiRs in Development of Cancer Stem Cell Populations in Colorectal Cancer

Abstract: MicroRNAs (miRNAs or miRs) have a critical role in regulating stem cells (SCs) during development and altered expression can cause developmental defects and/or disease. Indeed, aberrant miRNA expression leads to wide-spread transcriptional dysregulation which has been linked to many cancers. Mounting evidence also indicates a role for miRNAs in the development of the cancer SC (CSC) phenotype. Our goal herein is to provide a review of: (i) current research on miRNAs and their targets in colorectal cancer (CRC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 142 publications
(145 reference statements)
0
14
0
Order By: Relevance
“…Cancer stem cells (CSCs) have been classified as a small subset of tumor cells with the characteristics to influence self-renewal and differentiation, which makes it hard to eliminate the tumor [54]. CSCs have been identified in numerous solid tumors, such as breast cancer, colon cancer, and HCC [55][56][57]. We further analyzed the relationship of the expression of peroxisome-related genes with RNAss in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) have been classified as a small subset of tumor cells with the characteristics to influence self-renewal and differentiation, which makes it hard to eliminate the tumor [54]. CSCs have been identified in numerous solid tumors, such as breast cancer, colon cancer, and HCC [55][56][57]. We further analyzed the relationship of the expression of peroxisome-related genes with RNAss in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated the formation of G4 in the genomic cluster near three distinct microRNAs, namely, miR-23b, miR-27b, and miR-24 (cluster miR-23b-27b-24-1). The miR clusters can display tumor-suppressive or oncogenic roles depending on their context, as well as the individual members of the cluster that are able to adopt suppressor or oncogenic promoter behaviors according to the cancer type [77]. The authors found three potential G4 sequences capable of folding in antiparallel, and one in parallel, conformations, and tested six small molecules (tetrandrine, fangchinoline, palmatine, jatrorrhizine, berberine and cepharanthine; Scheme 1) [76].…”
Section: Rg4s In Mirnasmentioning
confidence: 99%
“…depending on their context, as well as the individual members of the cluster that are able to adopt suppressor or oncogenic promoter behaviors according to the cancer type [77]. The authors found three potential G4 sequences capable of folding in antiparallel, and one in parallel, conformations, and tested six small molecules (tetrandrine, fangchinoline, palmatine, jatrorrhizine, berberine and cepharanthine; Scheme 1) [76].…”
Section: Rg4s In Mirnasmentioning
confidence: 99%
“…Although the specific mechanism underlying microRNA deregulation in cancer has yet to be determined, multiple studies have demonstrated that epigenetic mechanisms play a significant role in the regulation of microRNA expression in cancer cells [13][14][15], particularly DNA methylation, which is a biological process that adds methyl groups (CH 3 ) to the cytosine ring, thus producing 5-methylcytosine (5mC) (Figure 1a). Expression of microRNAs might be epigenetically regulated via DNA methylation of CpG islands located at promoter regions [13] (Figure 1b,c).…”
Section: Introductionmentioning
confidence: 99%